DESAIN DERMAGA MULTI PURPOSE TIPE DECK ON PILE DI PULAU SEMBILAN KABUPATEN SINJAI - Edianto Edianto; Ashury Ashury (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2019)
A harbor is a place where ships stop. In the port there are many activities carried out, such as loading and unloading goods and passengers from ships. The utilization of Kambuno Port, located on Kambuno Island, Sinjai Regency, is no longer effective. The port is small and can no longer serve the number of ships and passengers that increase every day. The purpose of this research is to plan a deck on a piling type harbor located in Sinjai Regency. The analysis includes workload, design water level, and harbor dimensions. harbor dimensions. The data consists of primary and secondary data. After obtaining all the required data, it will be analyzed through several stages of ship design, presenting wind data, presenting topographic data, presenting bathymetry data, and presenting hydroboceanographic data (tides, wave currents, wave generating, design water level, and return period. water level, and return period. The workload consists of live load and death load. Based on the analysis, the total live load is 33.37tons and the total mortality load is 3,726.44 tons, where the water level is 1.07m. The dimensions of the harbor are length 68 m, and 8 m wide. Based on the analysis results, the dimensions of the slab are 68m x 8m x 0.30m, block 0.50mx 0.70m, pile cap is 1.00 x 1.00 x 1.00 m, and the pile is 0.4572 m in diameter and 0.012 m thick.